2022
DOI: 10.1155/2022/1085577
|View full text |Cite|
|
Sign up to set email alerts
|

Application of LSTM Neural Network Technology Embedded in English Intelligent Translation

Abstract: With the rapid development of computer technology, the loss of long-distance information in the transmission process is a prominent problem faced by English machine translation. The self-attention mechanism is combined with convolutional neural network (CNN) and long-term and short-term memory network (LSTM). An English intelligent translation model based on LSTM-SA is proposed, and the performance of this model is compared with other deep neural network models. The study adds SA to the LSTM neural network mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…How to design a loss function that can effectively capture both content and style information is a key issue. Traditional image style transformation methods usually require a lot of computational resources and time, making them unsuitable for real-time applications [14]. How to improve real-time performance and efficiency, especially on embedded devices, is an important challenge.…”
Section: Problem Analysismentioning
confidence: 99%
“…How to design a loss function that can effectively capture both content and style information is a key issue. Traditional image style transformation methods usually require a lot of computational resources and time, making them unsuitable for real-time applications [14]. How to improve real-time performance and efficiency, especially on embedded devices, is an important challenge.…”
Section: Problem Analysismentioning
confidence: 99%
“…For example, Xiang et al [21] used deep learning techniques, principally based on a blend of long short-term memory (LSTM) and CNN, for quick target extraction from films. Yang et al [22] integrated a standard target detector with an LSTM module to further enhance the detection performance of intelligent driving. In response to recent developments in computer vision, Mallick et al [23] substituted the gated recurrent units (GRU) for LSTM as a decoder in image captioning models.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%